2023
DOI: 10.1186/s12885-023-10520-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and label-free detection of gastrointestinal stromal tumor via a combination of two-photon microscopy and imaging analysis

Abstract: Background Gastrointestinal stromal tumor (GIST) is currently regarded as a potentially malignant tumor, and early diagnosis is the best way to improve its prognosis. Therefore, it will be meaningful to develop a new method for auxiliary diagnosis of this disease. Methods Here we try out a new means to detect GIST by combining two-photon imaging with automatic image processing strategy. Results Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…For example, Chen et al used multiphoton imaging to study the collagen characteristics of gastric tumor microenvironment and successfully uncovered optical markers of lymph node metastasis [32]. Li et al used MPM to image gastrointestinal stromal tumor and found significant differences in collagen fibers between normal and cancerous regions [33]. In this study, we found that SHG imaging can be used to accurately identify the different stages of fibrosis and to monitor the spatial distribution of collagen fibers during disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chen et al used multiphoton imaging to study the collagen characteristics of gastric tumor microenvironment and successfully uncovered optical markers of lymph node metastasis [32]. Li et al used MPM to image gastrointestinal stromal tumor and found significant differences in collagen fibers between normal and cancerous regions [33]. In this study, we found that SHG imaging can be used to accurately identify the different stages of fibrosis and to monitor the spatial distribution of collagen fibers during disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…1 A). Then, we developed an automatic image processing method to quantitatively analyze collagen changes in SHG images [ 24 , 25 ]: a Gaussian mixture model-based segmentation algorithm was used to segment SHG images into collagen fibers and background; afterwards, to track each fiber, we used a mature fiber network extraction algorithm to process the binary mask image of collagen fibers. After fiber extraction, the skeleton of each fiber was identified and represented by a list of ordered vertices, and if any vertex in the list belongs to more than one fiber, it would be identified as a cross-link point.…”
Section: Methodsmentioning
confidence: 99%
“…As described previously, we employed a commercial laser scanning confocal microscopy (LSM 880, Zeiss, Germany) in conjunction with a mode-locked femtosecond Ti: sapphire laser (Chameleon Ultra, Coherent, USA) to conduct multiphoton imaging [8][9][10]. A Plan-Apochromat 20×objective (NA = 0.8, Zeiss, Germany) was employed to acquire multiphoton images.…”
Section: Multiphoton Imagingmentioning
confidence: 99%